2019
DOI: 10.3390/ma12203395
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dentin Bonding Agents, Various Resin Composites and Curing Modes on Bond Strength to Human Dentin

Abstract: This study investigated the influence of several dentin bonding agents, resin composites and curing modes on push-out bond strength to human dentin. 360 extracted caries-free third molars were prepared, cut into slices, embedded in epoxy resin and perforated centrally. One half of the specimens (180) were treated by using one-step adhesive systems and the other half (180) with multi-step adhesive systems. Subsequently, the cavities were filled with either universal, flowable or bulk-fill resin composite accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 42 publications
(46 reference statements)
0
11
0
Order By: Relevance
“…Although the first-year damage rate of the FC seemed higher than that of the PC, the results of survival data considering the clustering effect showed no significant difference between the two composites. Although an FC was reported to have higher bond strength than a PC in an in vitro study, 9 it showed similar clinic performances from a 1-year clinical evaluation of an FC and a PC used as an occlusal restorative material. 16 In addition, the bond damage rate and survival time were affected not only by the bond strength but also by patients' habits and diets.…”
Section: Methodsmentioning
confidence: 80%
See 1 more Smart Citation
“…Although the first-year damage rate of the FC seemed higher than that of the PC, the results of survival data considering the clustering effect showed no significant difference between the two composites. Although an FC was reported to have higher bond strength than a PC in an in vitro study, 9 it showed similar clinic performances from a 1-year clinical evaluation of an FC and a PC used as an occlusal restorative material. 16 In addition, the bond damage rate and survival time were affected not only by the bond strength but also by patients' habits and diets.…”
Section: Methodsmentioning
confidence: 80%
“…It has been reported that FCs have a higher bond strength than PCs do. 9 In previous studies, precision of the attachment fit in vitro 10 and surface wear 11 of different composites in the clinic were investigated. However, few studies reported the operating time and attachment damage rate of different materials in CA treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The light curing offers the clinical advantage of extended working time, thus promoting precise material placement. However, the curing conditions such as exposure time, mode, energy density and exposure distance could have impact on the mechanical properties of the composite resins 10 . In this study, we performed the light irradiation protocol in strict accordance with the manufacturer's instructions to ensure that the composite resins were fully cured.…”
Section: Discussionmentioning
confidence: 99%
“…An earlier study showed that the bond strength to dentin was dependent on the composition of the restorative material [ 41 ] due to mechanical properties [ 42 ] or surface free energy characteristics of composites [ 43 ]. Steiner et al [ 44 ] ascertained that the strongest influence on bond strength was exerted by the resin composite type, followed by the adhesive system, while the choice of the curing intensity was not significant. Therefore, it is essential to collect data about the bond strength of all composite materials becoming available on the market.…”
Section: Discussionmentioning
confidence: 99%